Entrepreneurial Orientation and Performance of Small and Medium Scale Enterprises (SMEs) in Ikeja, Lagos State, Nigeria: Array - Ademosu, Akinwande; Morakinyo, Akinola (Acta Universitatis Danubius. Œconomica, 2021)
The study investigates the relationship between EO and SMEs’ performance using 96 SMEs in Ikeja, Lagos State, Nigeria. The three domains of EO namely innovation, pro-activeness and risk-taking are the focus of the study. Structured questionnaire is used to elicit responses from the SMEs’ entrepreneurs. The responses are subjected to both descriptive and inferential analysis under quantitative technique. The result from the analysis shows that strong synergy exists between risk-taking and pro-activeness. Findings further indicate that for EO to have significant impact on SMEs’ performance, the orientation of the entrepreneurs must be the one that brings about a strong connection between their drives for risk- taking and pro-activeness. This means that SMEs’ entrepreneurs should not only take risk or innovate but must be proactive with the two to achieve sustainable outstanding performances in their businesses